2004
DOI: 10.1111/j.1440-1703.2003.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of urbanization on ant distribution in parks of Tokyo and Chiba City, Japan I. Analysis of ant species richness

Abstract: To investigate how progressive urbanization influences the distribution of ant species in cities, I compared the ant species richness in urban parks of different areas and ages of Tokyo, the most intensively developed urban region in Japan, and its developing neighbor, Chiba City. A total of 43 ant species were found from 98 parks. Multiple regression analysis revealed that park area and age had a positive effect on the number of ant species in the parks and that the parks in Tokyo contained fewer species than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 17 publications
3
51
2
3
Order By: Relevance
“…Assim, os dois fragmentos parecem possuir nichos de alimentação e de nidificação semelhantes, o que pode estar relacionado ao tamanho das duas áreas. Segundo HÖLLDOBLER & WILSON (1990) e ROSENZWEIG (1995, áreas maiores podem favorecer maior oferta de nichos disponíveis e de recursos e, consequentemente, haverá maior número de espécies (YAMAGUCHI, 2004).…”
Section: Discussionunclassified
“…Assim, os dois fragmentos parecem possuir nichos de alimentação e de nidificação semelhantes, o que pode estar relacionado ao tamanho das duas áreas. Segundo HÖLLDOBLER & WILSON (1990) e ROSENZWEIG (1995, áreas maiores podem favorecer maior oferta de nichos disponíveis e de recursos e, consequentemente, haverá maior número de espécies (YAMAGUCHI, 2004).…”
Section: Discussionunclassified
“…performed at a single point in time along a gradient of urbanization (e.g., urban vs. rural areas, urban periphery vs. inner city, and urban green spaces vs. residential areas), or surveys have been conducted in several sites that have similar environmental condition (Yamaguchi 2004, Stringer et al 2009). While these approaches have allowed us to simplify the complicated effects of urbanization (Antonova 2005) and increased our understanding of the impact of invasive species on native communities (Touyama et al 2003, Stringer et al 2009), these approaches also have shown several associated problems.…”
Section: Study Areamentioning
confidence: 99%
“…For example, in this environment, many species achieve high densities, and assume dominant positions due to the existence of unoccupied niches, absence of competitors, and few natural enemies (Luck and Dahsten, 1974); or the intentional and unintentional introduction of exotic species can cause the dislocation of native species (Suarez et al, 1998;Crooks and Soulé, 1999). Yamaguchi (2004Yamaguchi ( , 2005, studying the influence of urbanization on ant distribution in parks, suggested that these insects would become the bio-indicators of variation in urban environments.…”
Section: Introductionmentioning
confidence: 99%